2020
DOI: 10.1101/2020.08.16.20176206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and associated factors of burnout in allied healthcare professionals in a tertiary hospital in Singapore

Abstract: Objective To explore the prevalence of burnout, factors associated with burnout, and barriers to seeking psychological help among allied health professionals in Singapore. Design Cross-sectional study. Setting A tertiary hospital in Singapore. Participants Allied health professionals. Primary outcome measure Burnout measured by using Maslach Burnout Inventory (MBI-HSS) Results: In total, 328 participants completed the questionnaire. The prevalence of burnout was 67.4%. A majority of the respondents were femal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The PT could have reflected lower empathy levels due to added workload and stress stemming from either caring for COVID patients, 33 or covering duties for colleagues. Studies in Singapore have shown the adverse effects of increased workloads among allied healthcare workers, manifesting in burnout 34 and the association between empathy and burnout. 23 Studies in Singapore have also reported a high prevalence of burnout among medical residents 23,30 and its association with lower empathy.…”
Section: Discussionmentioning
confidence: 99%
“…The PT could have reflected lower empathy levels due to added workload and stress stemming from either caring for COVID patients, 33 or covering duties for colleagues. Studies in Singapore have shown the adverse effects of increased workloads among allied healthcare workers, manifesting in burnout 34 and the association between empathy and burnout. 23 Studies in Singapore have also reported a high prevalence of burnout among medical residents 23,30 and its association with lower empathy.…”
Section: Discussionmentioning
confidence: 99%